2019
DOI: 10.1016/j.athoracsur.2019.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Vs Thoracotomy Sleeve Lobectomy for Lung Cancer: A Propensity Matched Analysis

Abstract: Background. In this retrospective study, we evaluated the safety and efficacy of video-assisted thoracic surgery (VATS) sleeve lobectomy for patients with centrally located non-small cell lung cancer. Methods. All consecutive patients who received VATS sleeve lobectomy (n [ 54) and thoracotomy sleeve lobectomy (n [ 94) were analyzed retrospectively; after propensity score matching, 78 paired cases were selected for further statistical analysis. Results. Among all patients, the VATS group showed significantly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 28 publications
5
53
2
1
Order By: Relevance
“…This study showed that the local recurrence rate after VATS sleeve resection was 0%. These survival and recurrence outcome were comparable to the outcomes of conventional sleeve lobectomy in the literature [1,5,12,14,15,24,25]. In 2013, Kasprzyk et al [26] have reported that the 5-year survival rate after conventional sleeve lobectomy was 56.1%, and the local recurrence rate was 9.3%.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This study showed that the local recurrence rate after VATS sleeve resection was 0%. These survival and recurrence outcome were comparable to the outcomes of conventional sleeve lobectomy in the literature [1,5,12,14,15,24,25]. In 2013, Kasprzyk et al [26] have reported that the 5-year survival rate after conventional sleeve lobectomy was 56.1%, and the local recurrence rate was 9.3%.…”
Section: Discussionsupporting
confidence: 67%
“…Since the first case report on the use of VATS sleeve lobectomy, published in 2002 [7], it has been used steadily by some thoracic surgeons [8][9][10][11]. Some retrospective studies have shown that VATS sleeve lobectomy is a safe and feasible surgical procedure for treating centrally located NSCLC with comparable perioperative and survival outcomes to the thoracotomy approach [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…By increased experience, more complex cases are dared to be performed by thoracic surgeons, such as sleeve resections, operations in patients who have received neoadjuvant treatment, chest wall invasions and pneumonectomies. [13][14][15][16] According to Li et al, [15] a thoracic surgeon should perform between 100 and 200 VATS resections to achieve efficiency. Over time, we aim to enhance our experience with cases and attempt VATS resections in larger and more complicated cases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recurrence-free survival and overall survival were better in patients who underwent VATS resection, even though the difference did not reach statistical significance. Gao therefore claimed that VATS sleeve lobectomy was a safe procedure, with oncological outcomes comparable to those after thoracotomy sleeve lobectomy and a faster postoperative recovery (55). It should also be considered that the more rapid healing after VATS surgery could lead to an earlier start of adjuvant chemotherapy, which in these cases is often indicated (56).…”
Section: Discussionmentioning
confidence: 99%